Analisis Struktur Bawah Permukaan menggunakan Data Satelit Gravitasi GGMPlus di Pulau Enggano, Bengkulu Utara Provinsi Bengkulu - Muhammad Deni Apriyanto; Refrizon Refrizon; Arif Ismul Hadi; Laura Nurul Aprilia Simamora; Siti Herfina Anjani (Jurnal Fisika Unand, 2026)
This study aims to identify subsurface structures and rock type in Enggano Island, North Bengkulu, using GGMPlus satellite graity data. The methods applied include the calculation of ABL with SRTM2gravity topographic correction, spectral analysis to estimate anomaly depth, and separation of regional and residual anomalies using the moving average method. Furthermore, two-dimensional modelling was conducted to obtain subsurface density distribution. The results show that the ABL values range from -20 mGal to 80 mGal, with low anomalies dominating the northern part and gradually increasing towards the south. Spectral analysis indicates that the average depth of regional anomalies is approximately 1875.7 m, while residual anomalies are about 123.27 m. The interpretation reveals that the northern area is dominated by low-density rocks, whereas the central to Southern parts are characterized by high-density rocks. The 2D modelling suggest the presence of sedimentary rocks, limestone, and igneous rocks (mafic intrusions), as well as fault structures or basin boundaries in the study area.